2009
DOI: 10.1128/iai.00295-09
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cells in Old Mice Contribute to the Innate Immune Response toMycobacterium tuberculosisvia Interleukin-12p70-Dependent and Antigen-Independent Production of Gamma Interferon

Abstract: Elderly individuals have increased morbidity and mortality associated with infectious diseases due in part to the progressive age-associated decline in immune function. Despite this, the old mouse model of Mycobacterium tuberculosis infection has revealed a CD8-and gamma interferon (IFN-␥)-dependent early resistance to infection. In this study, we investigated the mechanism by which CD8 T cells from old mice contributed to the early immune response to M. tuberculosis. Following a low-dose aerosol infection wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
7
27
0
Order By: Relevance
“…19 In support of our earlier study, Vesosky et al have identified the SET-PP2A interplay as being one possible mechanism by which CD8 T cells from aged mice produce enhanced levels of IFN-␥ in response to Mycobacterium tuberculosis after IL-12 and IL-18 stimulation. 27 In the current study, we hypothesized that SET could regulate NK cell-mediated cytotoxic activity via its regulation of PP2A. Performing loss-or gain-of-function experiments, we confirmed our preliminary evidence that modulation of SET altered cytotoxic activity of the NK-92 cell line.…”
Section: Discussionsupporting
confidence: 73%
“…19 In support of our earlier study, Vesosky et al have identified the SET-PP2A interplay as being one possible mechanism by which CD8 T cells from aged mice produce enhanced levels of IFN-␥ in response to Mycobacterium tuberculosis after IL-12 and IL-18 stimulation. 27 In the current study, we hypothesized that SET could regulate NK cell-mediated cytotoxic activity via its regulation of PP2A. Performing loss-or gain-of-function experiments, we confirmed our preliminary evidence that modulation of SET altered cytotoxic activity of the NK-92 cell line.…”
Section: Discussionsupporting
confidence: 73%
“…IFN-γ mRNA expression was associated with increased SET mRNA expression. Along these lines IL-18/IL-12 induced IFN-γ production by murine CD8 + was inhibited by forskolin, a known PP2A activator, which also decreased p-STAT4 levels [49]. Since FTY720 and not FTY720-P is known to bind a hydrophobic pocket of SET that leads to SET inactivation and PP2A activation, our data indicate that FTY720 inhibits IFN-γ via this pathway.…”
Section: Fty720 Inhibits Ifn-γ Formation Via the Set/pp2a Pathwaysupporting
confidence: 57%
“…Downstream of SET, active PP2A may then dephosphorylate and inhibit IFN‐ γ related transcription factors, e.g. IFN‐ γ related pSTAT1 and pSTAT4 . Ntranos et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the failure of old mice to control M. tuberculosis infection, subsequent work demonstrated that upon low-dose infection, old mice possessed a transient early resistance to M. tuberculosis that was mediated by CD8+ T cells [39], [40]. Turner has therefore proposed a model whereby old mice are able to mount an early innate response, but delayed generation of an adaptive immune response results in higher bacterial burden and inflammation [41]. Further investigation into the mechanisms of effective immune control of M. tuberculosis and application of this knowledge to the benefit of the elderly population is necessary.…”
Section: Discussionmentioning
confidence: 99%